Despossuídas do século XXI : mulheres no mercado de drogas no Brasil na última década (2006-2016) - Duarte, Joana das Flores (2019)
177 years after the publication of Marx (2017) articles in the Gazeta Renana, in the European context, his contribution remains not only current, but necessary to understand social processes in the Latin American and peripheral context. Situating the historicity of the work and the Brazilian reality, the purpose of rescuing it is precisely to show the barbaric face of capitalist accumulation, which is even more acute with regard to people in situations of criminalization by the State. This is because in the condition of violating the law, the woman becomes the object of sanction and punishment, and from her is not only suppressed the right to freedom, but also the right to be a protagonist of resistance, from antagonistic drive to the capitalist mode of production. This means that insofar as the state puts the person in the condition of defendant, the right to conflict against the oppressions of the state and capital society is also withdrawn. Because it is breaking the law, it is now considered a lesser person and therefore unable to be in the field of political disputes and battles. Criminalization and punishment, thus, are not restricted to acts of punishing only through prison, but above all, the political and collective life of the subject. It depoliticizes it to the point of not being seen as a human person, able to still require in the condition of "criminal" a place of respect and rights. The abstract law becomes concrete through its negation, that is, the woman prisoner only knows the rule of law when it violates her system of legal norms, so her punitive face is made by making her legally and criminally dispossessed. In addressing drug trafficking as a market, we affirm that it is based on an invisible workforce regarding the guarantee and enforceability of rights, not only that, but liable to criminalization. Thus, men and women, mostly young, black, with low education and survivors of the slums and peripheries, now occupy this illicit and informal work space formed in their spatialities. The illicit is the legal guarantee of capital control over them, because thus the appropriation and exploitation of the labor force occurs under two imminent risks: death and imprisonment. Given the legal and criminal structure, it is necessary to apply it in time and space, so it is necessary that subjects and places match the proposal of segregation and criminalization. Given this context, the thesis problem was: How are the determinants of gender, class and race expressed in the imprisonment of women arrested for drug trafficking in productions linked to graduate programs in the last decade (2006-2016) in Brazil? The general objective of the study was to analyze the relationship of the determinants of gender, class and race in the imprisonment of women for drug trafficking in the production of theses and dissertations linked to postgraduate programs in federal and state universities in the last decade (2006-2016) in Brazil. Regarding the specific objectives, we highlight: a) To identify the relationship between unemployment and the entry of women into drug trafficking in productions linked to graduate programs in federal and state universities in the last decade (2006-2016), in the Brazil; b) Identify the discourses on the insertion of these women arrested for drug trafficking in the production of theses and dissertations linked to postgraduate programs in federal and state universities in the last decade (2006-2016) in Brazil. c) examine the determinants of class, race and gender present in the production of theses and dissertations linked to postgraduate programs at federal and state universities in the last decade (2006-2016) in Brazil. We opted for postgraduate productions (dissertations and theses), from federal and state universities, in the five regions of the country, between 2006-2016, whose main research theme was the entry of women in the informal market. and illicit drugs. The search was performed at the Brazilian Digital Library of Theses and Dissertations (BDTD) with the descriptor “Women and Drug Trafficking”. There were 91 productions that were reduced to 12 productions based on the criteria listed, which had interviews with women arrested for the crime of drug trafficking. The material analysis process was performed based on the questions formulated by Volóchinov (2017, p. 220). This process was subdivided into 4 moments: I) reading and filing each material guided by the script, which consisted of analyzing the expectations that the speakers (reader) have regarding the comprehension of what they say to the interlocutors ( here authors); II) reading the file and articulation with the keywords of each text and the intentions of the interlocutors; III) access to the interview script of each production, its relation with the general objective of the respective text, situating the analysis of the existing dialogue between a current discourse with other discourses of the past; IV) main categories emerged after the previous stages and dialogical analysis of a present discourse with discourses that it raises in the future; and V) access to women's narratives from categories and the analysis of statements in concrete communicative contexts. The results showed that the analyzed productions about women arrested for the crime of drug trafficking, in this thesis, although they advance in the denunciation of living conditions and violations of human rights, do not radicalize in the critique of the discourse that there is a female crime, which in terms of science and knowledge production tends to reinforce oppressive and expropriating structures by seeking to define a type of criminal woman. These multiple definitions of entering the drug market individually read, sometimes for love, sometimes for autonomy, sometimes for material need, separate the reality of these women from the social relations of production and reproduction of capital, because they focus mainly on the positivist perspective of the drug´s deviant behavior, rather than focusing on the system as an expression of the contradictory combination of progress and destruction. That said, based on this research, we sought to state that women who are in the drug market today do not enter in isolation for purely subjective, affective and / or family reasons. There must be a real demand, sustained in their material needs of life and existence, which according to them is a central reason for entry. Trafficking would not be sustained by the perfidy of the idea of entering only by power and command, because this place is not for everyone. It is necessary to understand that these women correspond to a mass of informal unemployed, with low education, young and non-young, mostly black, rejected by the capital, from the point of view of the assured labor relations, a situation that most of them are generationally unaware of, becoming the dispossessed of the 21st century.